Factors affecting anxiety among administrative officers working within the urgent protective action planning zone of a nuclear power station - Hori, Hiroko; Orita, Makiko; Taira, Yasuyuki; Matsunaga, Hitomi; Kudo, Takashi; Takamura, Noboru (PloS one, 2020)
The aim of this study was to clarify the factors affecting anxiety among administrative officers working within the urgent protective action planning zone of a nuclear power station to establish an effective education program on radiation and its health effects to help reduce anxiety in residents. We included 1,181 officers who worked at local authorities within the urgent protective action planning zone of Sendai Nuclear Power Station in Kagoshima Prefecture, Japan. Logistic regression analysis revealed that female sex (odds ratio = 2.33), working more than 21 years as an administrative officer (odds ratio = 1.49), lack of participation in training on nuclear disasters (odds ratio = 1.42), and not knowing the three principles of radiation protection (odds ratio = 1.36) were independently associated with anxiety among administrative officers working within the urgent protective action planning zone. It is important to establish an effective education program on radiation and its health effects for administrative officers working within the urgent protective action planning zone to reduce anxiety in residents.